Retorika: Dari Filsafat Yunani Menuju Komunikasi Dakwah Modern - Nasution, Naufal Rifqi (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2023)
This article aims to explain the definition of rhetoric, trace its historical development from the classical to the modern era, and examine the relationship between rhetoric and communication in the context of da’wah. The research method used is qualitative libray reseacrh with a historical and content analysis approach. The main theoritical framework is based on Aristotle’s classical rhetoric, which includes ethos, pathos, and logos. The findigs indicate that classical rhetoric serves as a crucial foundation for developing effective communication strategies in modern Islamic preaching. In practice, rhetoric not only functions as a tool for delivering messages but also shapes audience perception and response. By mastering rhetorical principles, preachers can convey their messages more effectively and communicatively. The implications of this study highlight the improtance of rhetorical skills for da’wah practitioners so that their messages are not only understood but also emotionally resonate and raise awareness among audiences in a meaningful way. Keywords : classical rhetoric, da’wah communication, persuasion, Arstotle.